Reconceptualising the governance of migration policy in Australia : from centralised to cooperative approaches - Jones, Stephen, stručnjak za poslovno upravljanje (Array, 2019)
This article offers a comprehensive assessment of the current trends in the governance arrangements of migrant settlement policy in Australia. It outlines the context of migrant policy as an important element of nation building and in contributing to the most multicultural society in the OECD. While immigration remains popular with the majority of Australians it is not without challenges in terms of coordination between levels of government to achieve effective outcomes. The lessons from Australia have relevance for other multilevel systems in terms of the need for cooperative approaches that combine top down and bottom up contributions from government agencies at all levels and non-government organisations. The article provides an analysis of governance issues from the perspective of the major stakeholders. The key question addressed in this paper is; what are the key challenges and opportunities of establishing cooperative approaches to immigration policy in a multilevel system? Issues involved in a potential transition of Australia’s immigration policy from a centralist approach to a more cooperative approach will be examined through the lens of a framework of analysis that consists of three scenarios for the structure of immigration policy: the centralist, the cooperative and the asymmetric scenarios.